Assessment of natural variations in letter formations incorporating master pattern of handwriting - Gupta, Shruti; Garg, Rakesh K.; Nath, Surinder (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Handwriting is made up of countless habitual patterns. An individual’s handwriting is made up of a complexity of habitual patterns that are repeated within a typical range of variation around the model patterns. The muscle coordination of these and perceptions of how an individual sense form helps each one to develop one’s own Master Pattern of writing. A total number of 540 60 samples from each age group — 30 samples each from males & females, has been collected from 9 different age groups. Three handwriting samples — two in present handwriting with a gap of 5–10 minutes between the two handwritings and one old or past handwriting sample collected from each individual gap ranged from 2–33 years between present and old handwritings.With the due effect of the findings gathered from the present investigation the cases lacking in contemporary handwritings can be undertaken with ease by taking into account the letters — ‘f, y, r and i’ which have a major effect of natural variations on them which in turn makes them unreliable and should be avoided in the process of comparison as well as while forming an opinion.
Keywords: natural variations; master pattern; unreliable; contemporary